Detection of glyphosate residues in companion animal feeds. (December 2018) - Zhao, Jiang; Pacenka, Steven; Wu, Jing; Richards, Brian K.; Steenhuis, Tammo; Simpson, Kenneth; Hay, Anthony G.
Abstract: The widespread adoption of genetically modified, glyphosate-tolerant corn and soybean varieties in US crop production has led to a dramatic increase in glyphosate usage. Though present at or below regulatory limits currently set for human foodstuffs, the concentration of glyphosate in companion animal feed is currently unknown. In the present study, 18 commercial companion animal feeds from eight manufacturers were analyzed for glyphosate residues using ELISA. Every product contained detectable glyphosate residues in the range of 7.83 × 10 1 –2.14 × 10 3 μg kg −1 dry weight, with the average and medians being 3.57 × 10 2 and 1.98 × 10 2 μg kg −1 respectively. Three products were tested for within-bag variation and six were tested for lot to lot variation. Little within-bag variation was found, but the concentration of glyphosate varied by lot in half of the products tested. Glyphosate concentration was significantly correlated with crude fiber content, but not crude fat or crude protein. Average daily intakes by animals consuming feeds containing the median glyphosate concentration are estimated to result in exposures that are 0.68–2.5% of the Allowable Daily Intake (ADI) for humans in the US and EU, which are 1750 and 500 μg kg −1 respectively. Consumption of the most contaminated feed, however, would result in exposure to 7.3% and 25% of the above ADIs, though the relevance of such an exposure to companion animals is currently unknown. Companion animal feeds contained 7.83 × 10 1 –2.14 × 10 3 μg kg −1 glyphosate which is likely to result in pet exposure that is 4–12 times higher than that of humans on a per Kg basis. Graphical abstract: Image 1 Highlights: All tested cat and dog foods contained detectable glyphosate. Total fiber correlated with glyphosate, suggesting a plant-based origin. Exposure to glyphosate via food consumption is likely higher for pets than humans.